Konsekuensi Social Media Marketing Activities Brand Kosmetik Ramah Lingkungan - Novita Novita; Fatik Rahayu; Robert Kristaung (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Increasing awareness of problems in the surrounding environment is one of the reasons why many people are increasingly concerned about the environmental impact of every product they use, including cosmetic products. Technological developments have a very important influence on the dissemination of information about environmentally friendly cosmetic products. The role of social media is very necessary in disseminating information about environmentally friendly cosmetic products. This research aims to analyze the influence of social media marketing activities on self-brand connections both directly and through the mediation of user engagement. This research distributed questionnaires to 235 respondents and used a non-probability method with purposive sampling technique. Data were analyzed using the SEM method with the help of SPSS and AMOS programs. This research hopes: (1) there will be a positive influence of SMMA on self-brand connections; (2) there is an influence of SMMA on self-brand connection if there is user engagement as a mediating variable.